Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1080/07391102.2021.1872420
|View full text |Cite
|
Sign up to set email alerts
|

Anin silicoanalysis of Ibuprofen enantiomers in high concentrations of sodium chloride with SARS-CoV-2 main protease

Abstract: 2020 will be remembered worldwide for the outbreak of Coronavirus disease (COVID-19), which quickly spread until it was declared as a global pandemic. The main protease (Mpro) of SARS-CoV-2, a key enzyme in coronavirus, represents an attractive pharmacological target for inhibition of SARS-CoV-2 replication. Here, we evaluated whether the anti-inflammatory drug Ibuprofen, may act as a potential SARS-CoV-2 Mpro inhibitor, using an in silico study. From molecular dynamics (MD) simulations, we also evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
(77 reference statements)
1
6
0
Order By: Relevance
“…Validation of the system developed by us was performed using the drugs disulfiram and ebselen for comparison. The activity of these substances correlates with previously published data in the literature. , In addition, based on previously published theoretical calculations, we used ibuprofen as a reference drug. This compound showed no activity at all against the main protease.…”
supporting
confidence: 56%
“…Validation of the system developed by us was performed using the drugs disulfiram and ebselen for comparison. The activity of these substances correlates with previously published data in the literature. , In addition, based on previously published theoretical calculations, we used ibuprofen as a reference drug. This compound showed no activity at all against the main protease.…”
supporting
confidence: 56%
“…In other "in vitro" studies it was demonstrated that Ibuprofen shows bactericidal and virucidal activity [26,27]. Through computational studies, it was recently suggested that Ibuprofen could interact with M-pro, the major protease present in Coronavirus [28].…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 uses the host cellular interactome for its replication. NaIHS inhibits in silico [23] and may inhibit in vitro [24,25] the SARS-CoV-2 main protease (Mpro).…”
Section: Mechanisms That Might Inhibit Sars-cov-2 Replicationmentioning
confidence: 99%
“…Cathepsin L: negative modulation by the inhibition of IL-6 [8] and the inhibition of the positive feedback loop among IL-6 [8], NF-kB [8] and STAT3 [8]; 7. Mpro inhibition in silico [23] and in vitro [24,25]; 8. Inhibition in silico of the proviral-factors: TYMP, PTGS2, C1S, CFB, IFI44, XAF1, CXCL2 and CXCL3 [26].…”
Section: Mechanisms That Might Inhibit Sars-cov-2 Replicationmentioning
confidence: 99%
See 1 more Smart Citation